Mechanopharmacology of Rho-kinase antagonism in airway smooth muscle and potential new therapy for asthma. (September 2020) - Wang, Lu; Chitano, Pasquale; Seow, Chun Y.
Graphical abstract: Abstract: The principle of mechanopharmacology of airway smooth muscle (ASM) is based on the premise that physical agitation, such as pressure oscillation applied to an airway, is able to induce bronchodilation by reducing contractility and softening the cytoskeleton of ASM. Although the underlying mechanism is not entirely clear, there is evidence to suggest that large-amplitude stretches are able to disrupt the actomyosin interaction in the crossbridge cycle and weaken the cytoskeleton in ASM cells. Rho-kinase is known to enhance force generation and strengthen structural integrity of the cytoskeleton during smooth muscle activation and plays a key role in the maintenance of force during prolonged muscle contractions. Synergy in relaxation has been observed when the muscle is subject to oscillatory length change while Rho-kinase is pharmacologically inhibited. In this review, inhibition of Rho-kinase coupled to therapeutic pressure oscillation applied to the airways is explored as a combination treatment for asthma.